SOCIAL SUPPORT IN PREGNANCY AND PARTURITION WITH MENTAL DISORDER - Jesica Mulyadi; Winarni Dian Dwiastuti Wisnu Putri (Journal of Psychiatry Psychology and Behavioral Research, 2022)
Pregnant and childbirth are two periods in woman’s cycle life and had risk of occurrence mental disorders. Good social support is one way to minimize it. This review will explain about mental disorders and effect social support for pregnant women and childbirth with mental disorders. This article will discuss a literature review. PubMed, Medline, PsycINFO, and Web of Science, were searched including research studies published in English using the referencing period between 2000 and January 2021. Pregnancy and childbirth are the time of positive expectation and times for psychological and physiological challenges. Social support is important to intervention about common mental disorders. Social support comes from family, partner relationships, friends, etc. Social support can reduces stress in women's pregnancy and childbirth and make them enjoy and happy with their periods.Keywords: mental disorder, social support, pregnancy, childbirth.